Multicausal analysis of the dropout of university students from teacher training studies in Andalusia - Ibáñez-Cubillas, Pilar; López-Rodríguez, Slava; Martínez-Sánchez, Isabel; Rodríguez, José Álvarez (Frontiers in Education, 2023)
The aim of this investigation is analysing the college dropout, focalising in students of education degrees of Andalusian universities. We had studied the different approaches that exists in the actual scientific literature about the reasons of this phenomenon, to give an answer and a solution to this fact that brings a lot of inconvenient to universities and to the society. For doing that, we applied a standardized instrument created by Velázquez y González (2017) that pretend to determine which are the factors associated to the permanence of the college students. The instrument was applied to 608 students of the first year of six Andalusian universities. Of these, 274 were studying Enfant education degree and 334 Primary education degree. The study shows that a large sample of the subjects interviewed responded with higher scores 3.83, stating the need to remain in their undergraduate studies, with few references to dropping out of the university. Some of the items that have obtained the highest ratings express their desire to graduate with honors, become a good professional and practice their profession within their field of work, among others.